TERMINAL SOLID SOLUBILITY OF Gd IN Fe (Biological Sciences - PJSIR, 2002)
The constitutional data on Fe-Gd system do not include precise values of the extent of solid solubili ty of Gd in Fe. On the basis of investigations on the changes in oc1iron transition temperature (as a function of Gd contents) it has been established  that  Gd  in  concentrations  up  to  0.2  at %  decreases th e tem perature  of  oc-y transition  and  its effect istherefore , as a stabilizer of y iron. Higher concentration of Gd in iron however , act as "bee" stabilizer by increasing the                                                                                                                                                                                                                                  ,oc-y  iron  transformation  temperature.  The  solid  solubility  of  Gd  in  oc-iron  at the  peritectoid  temperature  of 931°C  is-1.0 at %.